Dapagliflozin Use in Heart Failure with Reduced Ejection Fraction Accompanied by Type 2 Diabetes Mellitus: A Systematic Review - Sinta Dwi Juniar; Mochamad Yusuf Alsagaff; Pudji Lestari; Budi Susetyo Pikir (Universitas Airlangga, 2022)
Abstract: Heart failure patients with reduced ejection fraction (HFrEF) respond well to pharmacological therapy and show a better prognosis. Heart failure patients with reduced ejection fraction and type 2 diabetes who were given SGLT-2 inhibitor therapy showed a strong and consistent reduction in the risk of death and hospitalization. The therapy that has recently begun to be investigated for its benefits for heart failure from the SGLT-2 inhibitor class is Dapagliflozin. The systematic review aims to analyze the effect of Dapagliflozin on the prognosis of HFrEF patients with type 2 diabetes mellitus. Material and Methods: The literature was searched from e-database PubMed, ScienceDirect, and ClinicalTrial.gov. Quality assessment was done using the Critical Appraisal Skills Program (CASP) Randomized Controlled Trial Standard Checklist. Results: A total of 22,167 patients from 4 RCTs eligible studies were included. The analysis results of all of the included studies indicate that Dapagliflozin affected the patient's prognosis. Two studies discuss mortality and hospitalization, and two studies discuss symptoms, functional status, and Quality of Life (QoL). Conclusion: Dapagliflozin can improve the prognosis of HFrEF patients with type 2 DM. The improved prognosis includes reduced mortality, reduced hospitalizations by minimizing disease worsening, reducing symptoms, improving functional status and QoL. Keyword: Cardiovascular disease, Dapagliflozin, Diabetes, Prognosis, SGLT 2 inhibitor